Cognitive and Language Function in Aphasic Patients Assessed With the Korean Version of Mini-Mental Status Examination - Kang, Eun Kyoung; Jeong, Hyun Sun; Moon, Eun Rhan; Lee, Joo Young; Lee, Kun Jai (Annals of rehabilitation medicine, 2016)
To assess the clinical usefulness of the relatively short instrument, the Korean version of the Mini-Mental State Examination (MMSE-K), for testing the association between cognition and language function in subacute post-stroke aphasia patients. Medical charts of 111 post-stroke patients (65 men; age 69.6±10.0 years; 124.6±80.6 days post-onset) were reviewed retrospectively. All patients were assessed longitudinally for aphasia using the validated Korean version of the Western Aphasia Battery (K-WAB) and for cognition using the MMSE-K. Patients were categorized and analyzed according to 3 aphasia-severity clusters. All subscales of the K-WAB showed significant improvement in follow-up assessments in all groups (p<0.05 or p<0.01). Only the scores of orientation, language function, and total score of MMSE-K showed significant improvement in all groups (p<0.01). The more severely impaired group showed stronger Pearson correlation coefficients between cognition and language function. Additionally, comparisons between correlation coefficients showed that the association of improvement in orientation with that of fluency and AQ% (aphasia quotient %) was significant in the more severely impaired group. Among subacute post-stroke aphasic patients, patients with more severe aphasia showed greater impairments to cognitive function; in addition, recovery of orientation may be related to recovery of language function.